Elementary School Students' Effectiveness towards Improving Mathematics Learning Outcomes in Additional Material - Judijanto, Loso; Supriyadi, Tugimin; Lumbantoruan, Jitu Halomoan; Jeranah, Jeranah (Mimbar Sekolah Dasar, 2023)
The low results of learning mathematics from year to year give rise to suggestions for students that mathematics is a difficult lesson. This needs to be researched to find out the relationship between mathematics learning attitudes, anxiety, habits, and additional mathematics learning outcomes. Quantitative research method with a survey approach. The subjects were 251 random sampling people. Data collection techniques using instruments adapted from Mathematics Learning Orientation which include attitudes, attention, and mathematics learning habits totaling 51 items. Analysis techniques using correlation and regression with SPSS software version 26.0. The findings show that attitudes, habits, and anxiety are positively and significantly related to mathematics learning. Mathematics learning anxiety has a moderate relationship, while mathematics learning attitudes and habits have a weak relationship to additional mathematics learning achievement. Another finding is that the relationship between anxiety about studying mathematics is the main predictor of additional material, compared to attitudes and habits about studying mathematics. The conclusion is that mathematics learning orientation is one of the factors that plays a very important role in determining the level of student achievement in mathematics. The contribution provides information that students who have a positive attitude in learning mathematics show good study habits, therefore the teacher's role is needed to build a positive attitude.